Robotic-assisted ileal ureter reconstruction: step-by-step guide - F. Eskenazi; A. Ardiles; L. Fumero; N. Otaño; L. Galvis; O. Rodriguez; R. Sotelo (Urology Video Journal, 2025)
Urolithiasis is one of the most common causes of urology consultation. Management for ureteral stones <10 mm can include observation and alpha-blockers. If unsuccessful, stones >10 mm, or complicated (obstructed or infected), definitive treatment may involve ureteroscopy, shock-wave lithotripsy, percutaneous nephrolithotripsy, or open or minimally invasive approaches. Selection will depend primarily on the location and size of the stone. Stones < 20 mm are best managed through ureteroscopy, which achieves a high stone-free rate in a single procedure, although not except for complications, which can occur in up to 25 % of cases. These include iatrogenic displacement of a ureteral calculus into the wall of the ureter, bleeding, perforation, stricture, and avulsion. In this video, we present a case of ureteral avulsion managed with robotic-assisted ileal ureter reconstruction, describing the step-by-step technique for a successful outcome.